Extending the spectrum of CLRN1‐ and ABCA4‐associated inherited retinal dystrophies caused by novel and recurrent variants using exome sequencing. Issue 3 (22nd January 2020) - Abu‐Ameerh, Mohammed; Mohammad, Hashim; Dardas, Zain; Barham, Raghda; Ali, Dema; Bijawi, Maysa; Tawalbeh, Mohamed; Amr, Sami; Hatmal, Ma'mon M.; Al‐Bdour, Muawyah; Awidi, Abdalla; Azab, Belal
Abstract: Background: Inherited retinal dystrophies (IRDs) are characterized by extreme genetic and clinical heterogeneity. There are many genes that are known to cause IRD which makes the identification of the underlying genetic causes quite challenging. And in view of the emergence of therapeutic options, it is essential to combine molecular and clinical data to correctly diagnose IRD patients. In this study, we aimed to identify the disease‐causing variants (DCVs) in four consanguineous Jordanian families with IRDs and describe genotype–phenotype correlations. Methods: Exome sequencing (ES) was employed on the proband patients of each family, followed by segregation analysis of candidate variants in affected and unaffected family members by Sanger sequencing. Simulation analysis was done on one novel CLRN1 variant to characterize its effect on mRNA processing. Clinical evaluation included history, slit‐lamp biomicroscopy, and indirect ophthalmoscopy. Results: We identified two novel variants in CLRN1 [(c.433+1G>A) and (c.323T>C, p.Leu108Pro)], and two recurrent variants in ABCA4 [(c.1648G>A, p.Gly550Arg) and (c.5460+1G>A)]. Two families with the same DCV were found to have different phenotypes and another family was shown to have sector RP. Moreover, simulation analysis for the CLRN1 splice donor variant (c.433+1G>A) showed that the variant might affect mRNA processing resulting in the formation of an abnormal receptor. Also, a family that was previously diagnosed with nonsyndromic RP was found to have Usher syndrome based on their genetic assessment and audiometry. Conclusion: Our findings extend the spectrum of CLRN1 ‐ and ABCA4 ‐associated IRDs and describe new phenotypes for these genes. We also highlighted the importance of combining molecular and clinical data to correctly diagnose IRDs and the utility of simulation analysis to predict the effect of splice donor variants on protein formation and function. Abstract : We identified novel and recurrent CLRN1 and ABCA4 disease‐causing variants in four Jordanian families with inherited retinal dystrophies. One of the ABCA4 variants was found in two unrelated families but surprisingly caused two different phenotypes.